If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + y + -3z = 4 Solving X + y + -3z = 4 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-1y' to each side of the equation. X + y + -1y + -3z = 4 + -1y Combine like terms: y + -1y = 0 X + 0 + -3z = 4 + -1y X + -3z = 4 + -1y Add '3z' to each side of the equation. X + -3z + 3z = 4 + -1y + 3z Combine like terms: -3z + 3z = 0 X + 0 = 4 + -1y + 3z X = 4 + -1y + 3z Simplifying X = 4 + -1y + 3z
| (4/5x)-3=5 | | 11n-(n^2)-24=0 | | 4y-24=12 | | 12x+16x+8x=180 | | ydx=x^2dy | | 6x-x^2+9+9-6x=18+12x-x^2 | | ln(3x)=7 | | (x+5)*(x+5)=9 | | 8x+10+10x+44=180 | | 2r-7s=7 | | ln(y)=-ln(x) | | 8x+x^2+16-8x-x^2+16=16x | | ax+a=b-bx | | 8x+x^2+16-8x-x^2+16=16 | | 20+4x=47-2x | | 8x+x^2+16-8x-x^2+16= | | 5x-8(4x-2)=-21 | | 2x=4-(x-5) | | -7x+6(7x)=0 | | y=31+3y+2+7 | | 6x=7y+21 | | (4/3x-2/5)^2 | | 2(2x-3)-3(4-x)=4(3x+2)-14 | | 2(2x-3)-3(4-x)=4(3x+2)-1 | | 3k+-5=13 | | 3x-3(-3x-3)=-15 | | 3x-2(4x-3)=5(3-x)-9 | | Y^3+y^2-90y=0 | | 2y^2+26y+144=0 | | -3x=52 | | 0.18(y-2)+0.16y=0.04y-0.9 | | -(5x^2y+2z)+2z-6x^2y= |